(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
As in the 19th century, forensic medical professionals are now primarily focused on the macroscopic picture of hemorrhage with subsequent microscopic examination. When studying micropreparations, the cellular composition of the hemorrhage is assessed based on known data, personal knowledge and experience, circumstances of the incident (if indicated in the referral for forensic histological examination), and the victim’s age.